PENGARUH TEKSTUR, KANDUNGAN AIR DAN SALINITAS TANAH TERHADAP KELIMPAHAN KERANG KEPAH (Polymesoda erosa) DI HUTAN MANGROVE DESA SUNGAI BAKAU KECIL KABUPATEN MEMPAWAH - Marwanto, Mitahul Rizqi; Anwari, M Sofwan; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2018)
Mangrove Forest in Sungai Bakau Kecil Village is located in Mempawah Timur District, Mempawah Regency. Mangrove ecosystem which has high economic and ecological value. Various species of mangroves, fish, shrimp, crabs and birds can be found in this area. The purpose of this study is to describe the influence of texture, water content and soil salinity to abundance of shellfish in mangrove forest Sungai Bakau Kecil Village Mempawah District. This research was conducted by using survey method, soil sampling technique and mangrove clam done purposively (purposive sampling). Soil samples were tested in the laboratory to see some observed parameters such as soil texture, soil water content, and salinity. Data analysis using descriptive. The texture of soil in mangrove forest of Sungai Bakau Kecil Village is a dusty clay loam soil classes. Soil texture does not determine the presence of shellfish in the mangrove forest of Sungai Bakau Kecil Village because the habitat of the shell is in the muddy or sandy ground. Shellfish can also live on the ground with dusty clay loam soil classes. Salinity suitable for shellfish with salinity value is 4.18 ppt, 4.27 pptdan 4.22 ppt with abundance of 3 / mÂ². The soil water content that determines the abundance of shellfish in the mangrove forest of Sungai Bakau Kecil Village with a range of values that is 36.57%, 41.33% and 50.61% with abundance 3 / mÂ² Other factors that influence the presence of shellfish is human activity which takes the shellfish in the forest and the seasonal factor also determines the amount of shellfish in the forest.Keywords: Abundance, Inland Water Content, Mangrove forest, Salinity, Texture.